Role of tourist destination development in building its brand image: A conceptual model - Manhas, Parikshat S. (2016)
Tourism is truly an international/global industry. Tourism is vital to the economy of a country and sustainable tourism development requires an understanding of the complex interrelationships and interactions among a multitude of environmental factors and interdisciplinary forces that play a critical role in tourism development. While overall the field of tourism has been abundantly researched there are certain areas where there is a paucity of research namely competition analysis branding and positioning. Our research contributes to this extremely important but relatively less researched subject. Specifically we study the relationship between destination development and its brand image. We develop a conceptual model which identifies various constructs processes and linkages involved in the relationship between destination development and its brand image. We propose that the brand image has three components corresponding to the three stages of consumption/travel namely pre-travel during travel and post-travel. In developing this model we draw upon the interdisciplinary nature of tourism and discuss a variety of influences such as economic social cultural political and psychological factors.